2012
DOI: 10.3109/09540261.2012.657613
|View full text |Cite
|
Sign up to set email alerts
|

Family environment, expressed emotion and adolescent self-harm: A review of conceptual, empirical, cross-cultural and clinical perspectives

Abstract: Self-harm in young people is a complex and pervasive problem with a number of co-existing risk factors. Although research has implicated a range of family variables in understanding the onset, maintenance and prevention of adolescent self-harm, relatively little attention has been given to the expressed emotion (EE) construct. Based on a narrative review and synthesis of peer-reviewed literature up to and including 2011, this paper considers the conceptual background and empirical evidence for the role of fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 95 publications
2
17
0
Order By: Relevance
“…Previous research has found high levels of EE within the family environment to be associated with self-harm and suicidal ideation in youth populations [ 34 ]. In our non-clinical adult sample, in line with predictions, self-injurers also reported higher levels of overall EE and greater perceived criticism (PC) compared to those with no history of self-injury, supporting previous research [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found high levels of EE within the family environment to be associated with self-harm and suicidal ideation in youth populations [ 34 ]. In our non-clinical adult sample, in line with predictions, self-injurers also reported higher levels of overall EE and greater perceived criticism (PC) compared to those with no history of self-injury, supporting previous research [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…While EE is traditionally assessed via the Camberwell Family Interview [ 30 ], recent studies have turned to more cost effective, shorter measures such as the Five Minute Speech Sample (FMSS) [ 31 ], the Level of EE Scale (LEES) [ 32 ], and the Family Emotional Involvement and Criticism Scale (FEICS) [ 33 ]. To date, studies of EE and self-harming behaviours have focussed on youth populations [ 34 ], all concluding that negative family environments characterised by high levels of EE lead adolescents to feel progressively depressed, hopeless, and trapped, in turn leading them towards self-harm and suicidal ideation as a means of escape. The Camberwell Family Interview, was used with families of Portuguese youth admitted to hospital following a self-harming episode (including excessive ingestion of substances) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were significantly less concerned about their adolescent's behaviour, more satisfied as parents, and less stressed and critical in their expressed emotion at follow-up. High expressed emotion in the family environment (encompassing critical, hostile and emotionally overinvolved behaviours and attitudes from caregivers) has been linked to a range of youth psychopathology, including conduct disorder,36 depression,37 anxiety38 and self-harm 39. Our study was probably underpowered to detect significant changes in adolescent mental health in association with improved family environment, especially since we recruited a non-clinical sample.…”
Section: Discussionmentioning
confidence: 98%
“…Self-injury becomes the last attempt to escape from the uncomfortable condition. The college students who injured themselves not only hoped to escape from their negative emotions, but also from negative self-belief (Michelson & Bhugra, 2012) through this behavior. Thus, this behavior is not only an effort to regulate emotions but also to punish themselves for perceived failure and purify the part of their self that they hate (Gratz & Chapman, 2009;Connor, 1996;Himber, 1994;Klonsky, Muehlenkamp, Lewis, & Walsh, 2011;Nock, 2009;Shearer, 1994;Zlotnick, Donaldson, Spirito, & Pearlstein, 1997) due to high self-criticism.…”
Section: Discussionmentioning
confidence: 99%